Processing and charcterization of a novel nonporous Poly(vinylidene fluoride) films in the beta-phase - Sencadas, Vítor João Gomes Silva (2006)
Poly(vinylidene fluoride) (PVDF) has remarkable properties leading to electro-optics, electro-mechanical and biomedical applications. In particular its piezo- and pyroelectric properties provide possibilities for many technological applications. The semicrystalline nature of PVDF, combined with the occurrence of at least four crystalline phases implies a complicated physical microstructure. The most frequently described and important phase is the β. The piezo and pyro-electric properties mainly depend on this phase, so increasing the β phase content has always been a great concern. It is possible to obtain films in the β phase by solution but this material presents a high porosity leading to an opaque appearance and a decrease of the mechanical an electrical properties. In this work, porous films in the β phase were obtained directly from the solution at 600C. After applying pressure perpendicular to the surface of the film at elevated temperature, the pores in the original sample are eliminated. The changes on the morphology and crystallinity associated to the pressure applied to the samples were also studied.